2015
DOI: 10.3389/fnana.2015.00124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative density of CCK- and PV-GABA cells within the cortex and hippocampus

Abstract: Cholecystokinin (CCK)- and parvalbumin (PV)-expressing neurons constitute the two major populations of perisomatic GABAergic neurons in the cortex and the hippocampus. As CCK- and PV-GABA neurons differ in an array of morphological, biochemical and electrophysiological features, it has been proposed that they form distinct inhibitory ensembles which differentially contribute to network oscillations and behavior. However, the relationship and balance between CCK- and PV-GABA neurons in the inhibitory networks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 132 publications
8
93
2
Order By: Relevance
“…CCK + INs were labeled for histochemistry and electrophysiology using an intersectional labeling approach. Our results are similar to previous studies before by our group and others [27,41,45,48,49]. We found that IPSCs recorded on BLA small CCK + INs co-express VIP, but their function is not known [37,51].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…CCK + INs were labeled for histochemistry and electrophysiology using an intersectional labeling approach. Our results are similar to previous studies before by our group and others [27,41,45,48,49]. We found that IPSCs recorded on BLA small CCK + INs co-express VIP, but their function is not known [37,51].…”
Section: Discussionsupporting
confidence: 93%
“…CCK + INs are also abundant in the mPFC, where they are the most common type of interneuron [49]. We next tested if CCK + INs in mPFC rely on N-type calcium channels to release GABA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on parvalbumin positive cells because of their abundance in hippocampus as compared to other interneuron types (Celio, 1986; Tamamaki et al, 2003; Whissell et al, 2015). In addition, parvalbumin positive interneurons phenotypes in adult P50 Bloc1s8 sdy/sdy hippocampus are shared with other interneurons, which we previously scored with diverse GABAergic transcript markers (Larimore et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Mice lacking e18a or De18a-only (Cacna1b tm4.1Dili ) were back crossed in C57BL/6 (Charles River) background for 6-8 generations, for details on how this mouse line was generated see [16]. To label CCK + INs with tdTomato (tdT), we performed intersectional genetic labeling as previously reported [22,23]. We utilized CCK-Cre (Cck tm1.1(cre)Zjh /J, Jax:012706) in C57BL/6 background, Dlx5/6-Flpe (Tg(mI56iflpe)39Fsh/J, Jax: 010815) in FVB/NJ background, and Ai65-D (B6;129S-Gt(ROSA)26Sort m65.1(CAG-tdTomato)Hze /J, Jax: 021875) in C57BL/6;I129 background mice.…”
Section: Housing Conditionsmentioning
confidence: 99%